Oxidative stress and antioxidative status of plasma and erythrocytes in patients with vivax malaria - Erel, O; Kocyigit, A; Avci, S; Aktepe, N; Bulut, V (Pergamon-Elsevier Science Ltd, 1997)
Objectives: To investigate the oxidative stress and antioxidative status of plasma and erythrocytes in patients with vivax malaria and healthy persons. Design and Methods: Activities of antioxidative enzymes, rates of pathways of hexose monophosphate shunt and purine salvage, levels of lipid peroxidation, reduced glutathione, methemoglobin and sulfhemoglobin of erythrocytes were determined. Lipid peroxidation and levels of antioxidant substances were measured. Results: Antioxidants levels and antioxidative enzymes activities were lower and lipid peroxidation, purine salvage rate were higher in patients group than controls. Erythrocyte glucose-6 phosphate dehydrogenase (G-6-PD) activity was not different from that of healthy subjects. Conclusions: Oxidative mechanisms were observed to be dominant compared with antioxidative mechanisms in patients with vivax malaria. Therefore, oxidative stress may be produced and maintained by the host defense mechanisms against malarial infection.
Keywords: malaria; oxidative stress; lipid peroxidation; methemoglobin; sulfhemoglobin; antioxidants; glutathione; G-6-PD; purine